Antimicrobial and CNS depressant activities of Premna obtusifolia R. Br. (Lamiaceae) - Md. Monirul Islam; Jesmin Akter; Md. Zakir Sultan; Mohammad Shawkat Ali (Bioactivities, 2025)
People in Bangladesh's rural areas have a long tradition of treating various diseases with medicinal plants. To investigate antimicrobial and central nervous system (CNS) depressant activity of Premna obtusifolia R. Br., the crude ethanolic extract of the whole plant with its various fractions (n-hexane, chloroform, and methanol soluble fractions) was used. The disc diffusion method was used to conduct an antimicrobial test at a dose of 400 µg/disc. Swiss albino mice's central nervous system activity was examined using the Open Field Test and Hole Cross Test at doses of 150 and 300 mg/kg BW. In the disc diffusion method, the various fractions didn’t show prominent antimicrobial activity. In the hole-cross test, a significant reduction (p < 0.05) in activity was observed at 30 min only for the higher dose of the crude extract and the methanol-soluble fraction. In contrast, both the n-hexane and chloroform-soluble fractions produced significant reductions at both dose levels tested. By 60 and 90 min, all treated groups exhibited statistically significant activity reduction compared to the control. Similarly, in the open-field test, all fractions significantly decreased the number of square visits at the 30-min mark. While the crude extract also reduced visits at 60 and 90 min, this effect was not statistically significant. The other fractions, however, maintained a significant reduction at these later time points. It is evident from the results above that different P. obtusifolia fractions have shown strong neuropharmacological potential in various in vivo experimental models. Therefore, it will be a possible source for a lead molecule that may be isolated to treat various diseases.